Biometric encryption using Co-Z Divisor Addition Formulae in Weighted Representation of Jacobean Genius 2 Hyperelliptic Curves over Prime Fields - Brumnik, Robert; Kovtun, Vladislav; Kavun, Sergii; Podbregar, Iztok (IntechOpen, 2011)
None